1996
DOI: 10.1891/0886-6708.11.4.277
|View full text |Cite
|
Sign up to set email alerts
|

A Large Sample Empirical Typology of Male Spouse Abusers and Its Relationship to Dimensions of Abuse

Abstract: A number of studies have described typologies of domestically violent men. Holtzworth-Munroe and Stuart (1994) recently proposed a theoretical model for predicting violence severity and generality from personality “type.” The present study, using data from 833 identified abusive men, tested the model. Personality types were determined from cluster analysis of data from the Millon Clinical Multiaxial Inventory, and resulted in a three-cluster solution consistent with the Holtzworth-Munroe and Stuart model. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
203
2
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(229 citation statements)
references
References 0 publications
21
203
2
3
Order By: Relevance
“…In a later empirical test of this hypothesized typology (using cluster analysis of measures of husband violence toward a partner, general violence, antisociality, and fear of abandonment), four clusters were identified, including the three hypothesized groups and an additional low-level antisocial group who fell between the family only and generally violent and antisocial group . Several studies have generally found support for the three group batterer typology (Hamberger, Lohr, Bonge, & Tolin, 1996;Langhinrichsen-Rohling, Huss, & Ramsey, 2000;Tweed & Dutton, 1998;Waltz, Babcock, Jacobson, & Gottman, 2000), although the number and characteristics of all the subgroups are still debatable . Holtzworth-Munroe at al.…”
Section: Principal Batterer and Violence Typologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a later empirical test of this hypothesized typology (using cluster analysis of measures of husband violence toward a partner, general violence, antisociality, and fear of abandonment), four clusters were identified, including the three hypothesized groups and an additional low-level antisocial group who fell between the family only and generally violent and antisocial group . Several studies have generally found support for the three group batterer typology (Hamberger, Lohr, Bonge, & Tolin, 1996;Langhinrichsen-Rohling, Huss, & Ramsey, 2000;Tweed & Dutton, 1998;Waltz, Babcock, Jacobson, & Gottman, 2000), although the number and characteristics of all the subgroups are still debatable . Holtzworth-Munroe at al.…”
Section: Principal Batterer and Violence Typologiesmentioning
confidence: 99%
“…Cavanaugh and Gelles (2005) summarize findings from batterer typology studies, including Gondolf (1988), Gottman et al (1995), Hamberger et al (1996), Holtzworth-Munroe and Stuart (1994), and Johnson (1995). They conclude that three types of batterers are common across current typology research--a low, moderate, and high-risk offender.…”
Section: Rethinking Conceptual Approaches To Understanding the Etiolomentioning
confidence: 99%
See 1 more Smart Citation
“…This research suggests a substantial prevalence of major disorders and their association with batterer program dropout and re-assault (Hamberger & Hastings, 1991;Hamberger et al, 1996;Gondolf, 1999b). Other research addressing distinguishing personality traits, batterer types, and risk assessment have also indirectly raised questions about psychopathology (e.g., Dutton, 1998;Holtzworth-Munroe & Stuart, 1994).…”
Section: Mental Disorders and Batterersmentioning
confidence: 92%
“…A few of these studies specifically indicate a high prevalence of psychopathology (i.e., DSM-IV Axis I disorders or DSM-IV Axis II disorders) among batterer program participants (Hamberger et al, 1996;Gondolf, 1999b). According to studies with the MCMI-I, as much as 40% of men entering programs show evidence of psychopathology, much of which might be expressed in the form of personality tendencies or disorders (Hamberger & Hastings, 1991;Hamberger et al, 1996).…”
Section: Mental Disorders and Batterersmentioning
confidence: 99%